Penerapan Augmented Reality Berbasis Marker Based Dalam Membangun Media Promosi Pada SMK Sulthan Muazzam Syah - Putri, Rahmi Apriana; Fatdha, T.Sy Eiva; Haryono, Dwi; Yenni, Helda (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
In the digital era, school promotion faces challenges in attracting prospective students. Conventional media such as brochures are less effective for generations who are accustomed to digital technology. This research aims to apply Marker Based Augmented Reality (AR) technology as a promotional media innovation at SMK Sulthan Muazzam Syah. The method used is Multimedia Development Life Cycle (MDLC) with six stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Implementation is done using MyWebAR, with system testing through black box testing, distance, light, and compatibility testing. The results show that the system functions optimally, with a System Usability Scale (SUS) score of 85, in the Acceptable category, Grade B, and Excellent rating. Integration with Instagram expands the reach of promotion. The application of Marker Based AR increases the effectiveness of information delivery, attracts the attention of prospective students, and provides a better interactive experience than conventional methods. This technology also serves as an innovative solution for other schools in strengthening promotional appeal in the digital era.